Caracterização química e capacidade antioxidante de infusão de mesocarpo (entrecasca) de coco verde (Cocos Nucifera Linn.): perfil de compostos fenólicos e ácidos orgânicos - Santos, Iris Conceição Sampaio (2021)
The use of bark and other plant residues, including fruits, for years has been used in traditional medicine to treat diseases. The green coconut husk corresponds from 80 to 85% of the gross weight of the fruit and despite being organic material, its natural decomposition takes time, so without reuse or improper disposal, it becomes an environmental problem due to the alarming accumulation. Therefore, the use of this residue for medicinal purposes would be a healthy alternative. The aim of this study was to determine the profile of phenolic compounds and organic acids in infusion of dehydrated mesocarp of green coconut (Cocos nucifera), and to evaluate the antioxidant activity in vitro. Initially, the green coconut mesocarp was separated and subjected to dehydration in an air circulation oven at 40°C for 72 hours. Then, the infusion was obtained for subsequent analyses. The mesocarp (core) of green coconut was characterized physicochemically (water activity - aw, ºbrix, ash, pH, moisture and acidity) and organic acids identified by high performance liquid chromatography (HPLC). Total phenolic compounds were quantified, using Folin Ciocalteau reagent, and total flavonoids in the infusion obtained from the dehydrated mesocarp and, having determined the profile of phenolic acids and flavonoids by HPLC, the results were expressed in mg of gallic acid equivalent (GAE) and quercetin (EQ) per gram of dry basis (BS), respectively. Finally, the antioxidant activity of the infusion was evaluated in different in vitro methods by spectrophotometry (DPPH radical scavenging, ABTS radical uptake, ferric ion reducing capacity - FRAP and oxygen radical absorbing capacity - ORAC). In the physical-chemical characterization of fresh green coconut mesocarp, the following results were found: aw 0.33; ºbrix 42.33; humidity 8.64%; ash 5.12%; pH 5.2 and acidity 9.13%. Among the organic acids were still identified in the mesocarp, oxalic acid (27.3 mg); quinic acid (75.3 mg); citric acid (4.0 mg); fumaric acid (0.5mg) and succinic acid (1.5mg). For the infusion obtained from dehydrated green coconut mesocarp, the total phenolics corresponded to 55.5 mg EAG/g BS and flavonoids, 35.3 mg EQ/g BS. A single flavonoid, epigallocatechin gallate, was identified. The green coconut infusion showed antioxidant activity, consisting of 50.29 ± 0.75 μM TE /100g for DPPH radical reduction, 229.71 ± 5.41 μM TE/100g for ABTS radical uptake, 126.16 ± 24.55 μM TE /100g in FRAP and 247.71 ± 14.54 μM TE /100g in ORAC. The phenolic compounds found could possibly attribute important therapeutic actions to the infusion of dehydrated green coconut. The presence of organic acids in the mesocarp can provide a good influence on the palatability of the infusion, and can be an effective and economical alternative source of natural antioxidant. The reuse of coconut husk (waste) mitigates the environmental impact caused. However, in vivo studies are necessary to prove the real effectiveness of the infusion of green coconut mesocarp in diseases of intestinal disorders, such as diarrhea, as well as to assess whether there is toxicity as part of the fruit is considered inedible.